<h3>
Answer: 123 meters is the longest </h3>
============================
Work Shown:
Convert everything to the same unit. I'm going to convert everything to meters
0.1203 km = 120.3 meters (multiply by 1000)
1230 cm = 12.3 meters (divide by 100)
12030 mm = 12.03 meters (divide by 1000)
------------------
The four distances we have are: 120.3 meters, 123 meters, 12.3 meters, 12.03 meters. We see that 123 meters is the longest.
Kriste respone is wrong
<em><u>Solution:</u></em>
Given that,
Kristen was asked to write each of the numbers in the expression 80,000 x 25 using exponents
Her response was (8 x 10 to the power of 3) x 5 to the power of 2
No, the response of Kristen is wrong
Let us first understand about exponents
An exponent refers to the number of times a number is multiplied by itself
Given expression is:
![80000 \times 25](https://tex.z-dn.net/?f=80000%20%5Ctimes%2025)
Here, 80000 has 4 zeros
Therefore, it can be raised as 10 power 4
![80000 = 8 \times 10^4](https://tex.z-dn.net/?f=80000%20%3D%208%20%5Ctimes%2010%5E4)
<em><u>Thus the expression becomes:</u></em>
![80000 \times 25 = 8 \times 10^4 \times 25](https://tex.z-dn.net/?f=80000%20%5Ctimes%2025%20%3D%208%20%5Ctimes%2010%5E4%20%5Ctimes%2025)
Also, 25 can be written as 5 power 2
![80000 \times 25 = 8 \times 10^4 \times 5^2](https://tex.z-dn.net/?f=80000%20%5Ctimes%2025%20%3D%208%20%5Ctimes%2010%5E4%20%5Ctimes%205%5E2)
Thus given expression is written as (8 x 10 to the power 4) x 5 power to the power 2
Thus Kristen respone is wrong, because he has raised 10 to power 3
Answer:
x = 1/4
y = -1/2
z = 9/4
Step-by-step explanation:
Here we have a system of 3 equations with 3 variables:
4*x + 2*y + 1 = 1
2*x - y = 1
x + 3*y + z = 1
The first step to solve this, is to isolate one of the variables in one of the equations, let's isolate "y" in the second equation:
2*x - y = 1
2*x - 1 = y
Now that we have an expression equivalent to "y", we can replace this in the other two equations:
4*x + 2*(2*x - 1) + 1 = 1
x + 3*(2*x - 1) + z = 1
Now let's simplify these two equations:
8*x - 1 = 1
7*x - 3 + z = 1
Now, in the first equation we have only the variable x, so we can solve that equation to find the value of x:
8*x - 1 = 1
8*x = 1 + 1 = 2
x = 2/8 = 1/4
Now that we know the value of x, we can replace this in the other equation to find the value of z.
7*(1/4) -3 + z = 1
7/4 - 3 + z = 1
z = 1 + 3 - 7/4
z = 4 - 7/4
z = 16/4 - 7/4 = 9/4
z = 9/4
Now we can use the equation y = 2*x - 1 and the value of x to find the value of y:
y = 2*(1/4) - 1
y = 2/4 - 1
y = 1/2 - 1
y = -1/2
Then the solution is:
x = 1/4
y = -1/2
z = 9/4
Answer:
Step-by-step explanation:35x
The equation given in the question is
13 + (w/7) = - 18
(91 + w) / 7 = - 18
91 + w = - 126
w = - 126 - 91
= - 217
I hope that the procedure is clear enough for you to understand. I also hope that this is the answer that you were looking for and the answer has actually come to your desired help.